2001
DOI: 10.1002/1521-3765(20010518)7:10<2245::aid-chem2245>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

FluorescentJ-type Aggregates and Thermotropic Columnar Mesophases of Perylene Bisimide Dyes

Abstract: A series of perylene tetracarboxylic acid bisimides 3a-e bearing 3,4,5-tridodecyloxyphenyl substituents on the imide N atoms and zero, two, or four phenoxy-type substituents in the bay positions of the perylene core were synthesized. From investigations of their spectroscopic properties and aggregation behavior in low-polarity solvents by absorption and fluorescence optical spectroscopy, not only were these compounds found to form fluorescent J-type aggregates, but also binding constants for aggregation could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
463
0
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 622 publications
(504 citation statements)
references
References 72 publications
34
463
0
7
Order By: Relevance
“…The same conclusions have also been outlined by Neuteboom and coworkers 79 when studying the optical features of polytetrahydrofuran substituted PBI polymers in ODCB. Arnaud et al, 71 Würthner et al, 70,80,81 Datar et al, 82 and Yagai et al 75 reported as well the formation of this red-shifted band due to selfassembled/polymeric PBI in solutions.…”
Section: Resultsmentioning
confidence: 99%
“…The same conclusions have also been outlined by Neuteboom and coworkers 79 when studying the optical features of polytetrahydrofuran substituted PBI polymers in ODCB. Arnaud et al, 71 Würthner et al, 70,80,81 Datar et al, 82 and Yagai et al 75 reported as well the formation of this red-shifted band due to selfassembled/polymeric PBI in solutions.…”
Section: Resultsmentioning
confidence: 99%
“…42 Many research groups have attempted to enhance the emission from the pyrene core in the solid state by modifying the molecular structures. 43 Sterically congested mesityl substituents can prevent undesirable face-to-face π-stacking, so that self-quenching is impeded to permit efficient emission.…”
Section: 11mentioning
confidence: 99%
“…[1][2][3][4] Perylene diimides (PDIs) derivatives effectively form supramolecular assemblies through p-p stacking interaction. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] In particular, supramolecular assemblies based on calixarenePDI conjugates show efficient energy and electron transfer properties due to the well-defined rigid and electron-rich scaffolds of calixarenes. [22][23][24][25][26][27] We have prepared PDI derivatives with a high emission property in aqueous solutions.…”
Section: Introductionmentioning
confidence: 98%